Pemberian Perlindungan dan Pemberlakuan Keadilan bagi Korban Kekerasan Seksual dalam Sistem Hukum Pidana Indonesia - San Mikael Sinambela; Manotar Leryaldo Sinaga; Reh Bungana Br Perangin-angin; Maulana Ibrahim (Universitas Sains dan Teknologi Komputer, 2024)
This research was conducted with the aim of understanding how the provision of protection and enforcement of justice for victims of sexsual violence is viewed from the perspective of criminal law in Indonesia. The research method employed was qualitative descriptive using a literature review approach. The results indicate that the provision of protection and enforcement of justice for victims of sexual violence has been consistently implemented in accordance with criminal law, with penalties for perpetrators commensurate with their actions. In conclusion, Indonesian criminal law affirms that any criminal act, especially sexsual violence, will be met with proportional punishment for the perpetrator, and enforcement will be carried out firmly and justly.